Kesiapan SMK dalam pelaksanaan uji kompetensi keahlian dalam rangka ujian nasional - Samsudi Samsudi (Jurnal Pendidikan Vokasi, 2011)
READINESS OF VOCATIONAL SCHOOL IN THE IMPLEMENTATION OF THE COMPETENCE TEST EXPERTISE IN THE FRAMEWORK OF NATIONAL EXAMINATIONCompetency examination in Vocational School national examination started in 2006/2007 needs researches, one of them is those regarding to the readiness and implementation in the field. It is based on the reality that the schools' conditions are vary, from locations, internal conditions, and stakeholders' supports. This reasearch's objective is to describe vocational schools' readiness on test location, internal accessors and examiners, infrastructures (rooms, materials, tools), time of implementation, length of time for competency examination, procedures, and mechanism. The discussion of those are divided into two locations, namely province and regency.